2021
DOI: 10.1016/j.jcmgh.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A Nucleotide Analog Prevents Colitis-Associated Cancer via Beta-Catenin Independently of Inflammation and Autophagy

Abstract: Background & Aims Chronic bowel inflammation increases the risk of colon cancer; colitis-associated cancer (CAC). Thiopurine treatments are associated with a reduction in dysplasia and CAC in inflammatory bowel disease (IBD). Abnormal Wnt/β-catenin signalling is characteristic of >90% of colorectal cancers. Immunosuppression by thiopurines is via Rac1 GTPase, which also affects Wnt/β-catenin signalling. Autophagy is implicated in colonic tumors, and topical delivery of the thiopurine thioguanine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…RAC1 appears as an attractive candidate in the context of malignancies. Taking advantage of in vivo experiments, it was shown that thiopurines treatments (TG) inhibited CAC in the AOM/DSS mouse model, via decreased β-catenin in a RAC1-dependent mechanism [ 144 ]. In the context of epithelial cell targeting, EMT and metastatic potential might be inhibited upon activation of RAC1; for instance, upon CSRP2 treatment (Hippo-ERK-PAK/LIMK/cortactin) [ 145 ], miR-142-3p transfection [ 146 ], upregulation of SSH3 (LIMK) [ 147 ] or PLS1 (ERK1/2) [ 148 ], downregulation of DMTN [ 149 ], or IRF1 suppression [ 150 ].…”
Section: Rac1 (Ras-related C3 Botulinum Toxin Substrate 1)mentioning
confidence: 99%
“…RAC1 appears as an attractive candidate in the context of malignancies. Taking advantage of in vivo experiments, it was shown that thiopurines treatments (TG) inhibited CAC in the AOM/DSS mouse model, via decreased β-catenin in a RAC1-dependent mechanism [ 144 ]. In the context of epithelial cell targeting, EMT and metastatic potential might be inhibited upon activation of RAC1; for instance, upon CSRP2 treatment (Hippo-ERK-PAK/LIMK/cortactin) [ 145 ], miR-142-3p transfection [ 146 ], upregulation of SSH3 (LIMK) [ 147 ] or PLS1 (ERK1/2) [ 148 ], downregulation of DMTN [ 149 ], or IRF1 suppression [ 150 ].…”
Section: Rac1 (Ras-related C3 Botulinum Toxin Substrate 1)mentioning
confidence: 99%
“…In addition, in vitro silencing experiments showed that TG suppression of b-catenin was dependent on Rac-1 at lower physiological concentrations, whereas it was Rac-1 independent at supraphysiological higher concentrations. 13 As a member of the Ras superfamily of Rho GTPases, GTP-bound Rac1 mediates a plethora of cellular processes including actin reorganization and gene transcription. It is possible that the TG Rac1 interaction may result in other cellular effects independent of b-catenin transcriptional activity, to inhibit CAC development, which warrants further investigation in future work.…”
Section: Q6mentioning
confidence: 99%
“…12 Blockade of Rac1 signaling by thiopurines results in suppression of proinflammatory T cell responses, mainly by induction of T cell apoptosis and impairment of synapse formation between T cells and antigen-presenting cells. 9,10 In this issue of Cellular and Molecular Gastroenterology and Hepatology, Sheng et al 13 investigate the role of TG in CRC, exploring how TG might alleviate colitis-associated cancer (CAC). Chronic inflammation that occurs in poorly controlled ulcerative colitis can promote CAC.…”
mentioning
confidence: 99%
See 2 more Smart Citations